Utilization of "Learning House" as A Technology-Based Media for Technology-Based Indonesian Learning - Apriani, Hamidah (Edunesia : Jurnal Ilmiah Pendidikan, 2023)
today. If it is used in education, its function is to convey teaching materials, one of which is by utilizing technology such as the internet to access several existing sources. This research aims to gain knowledge about the application of "Rumah Belajar" as a technology-based learning media for Indonesian. The role of technology is very important in the field of education today. In addition, teacher creativity is needed to create interesting learning media and facilities. The research method used in This research is descriptive. Data collection is done by reviewing the results of similar studies' pre-existing learning media and examining learning media Indonesian-based technology. Results show that One of the learning media that students guided by the teacher can use is the "Learning House" application. The learning house is one of the contents created by the Education and Culture Information Technology and Data Center (PUSDATIN) of the Ministry of Education and Culture (Kemendikbud). The conclusion from the study is that Learning House contains learning material content that can be utilized by educators and Early Childhood Education (PAUD) students, Elementary Schools (SD), to High/Vocational High Schools (SMA/SMK) as sources of learning media. With the jargon: Study anywhere, anytime, with anyone, "learning house" is easy to access